Examining the Integrated Effects of Online Reviews, Sensory Branding, Digital Marketing, and Pop Culture on Consumer Purchase Decisions - Reni Diah Kusumawati; Agung Prasetyo Wibowo; Himanshu Dutt (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study examines the influence of online reviews, sensory branding, digital marketing, and pop culture on consumer purchase decisions within Indonesia’s e-commerce environment. The research was motivated by the rapid growth of Indonesia’s digital economy and the increasing importance of digital consumer behaviour in online marketplaces. A quantitative research approach was employed using survey data collected from 125 online consumers with prior e-commerce purchasing experience. Data were analysed using multiple linear regression to evaluate the relationships between the independent variables and purchase decisions. The findings indicate that online reviews and sensory branding positively influence consumer purchase decisions, highlighting the importance of trust, credibility, and experiential engagement in digital shopping environments. In contrast, digital marketing and pop culture were not found to exert significant direct effects on purchase decisions. These results suggest that consumers rely more heavily on authentic peer-generated information and immersive online experiences than on conventional promotional content or broad cultural influences when making purchasing decisions. The model demonstrates strong explanatory power in predicting online consumer behaviour within Indonesia’s e-commerce sector. This study contributes to the consumer behaviour and digital marketing literature by integrating cognitive, experiential, promotional, and cultural dimensions within a single analytical framework based on the Stimulus–Organism–Response (S-O-R) model. The findings also provide practical implications for businesses by emphasising the importance of transparent review systems, engaging sensory-based digital experiences, and trust-oriented online marketing strategies to enhance consumer purchasing behaviour in emerging digital markets.